THE IMPACT OF A VENDOR-MANAGED INVENTORY POLICY ON THE CASH-BULLWHIP EFFECT - Sim, Jaehun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
It is essential to secure a sustainable flow of cash along the supply chain in the modern corporate environment. Due to the growing significance of cash flow, the concept of the cash-flow bullwhip effect has recently drawn academic attention to finding solutions to the cash shortage. The supply chain’s response to the bullwhip effect, known as the cash-flow bullwhip effect, causes cash-flow volatility to be amplified from downstream to upstream. A number of research studies have looked into the sources and effects of the cash-flow bullwhip effect, but none have concentrated on solutions. This study investigated for the first time the impacts of the vendor-managed inventory policy as a tool for mitigating the cash-flow bullwhip effect. The findings show that the vendor-managed inventory policy typically shortens the cash-conversion cycle of each supply chain member and can, therefore, be implemented as a policy for mitigating the cash-flow bullwhip effect.